Enhancing English Language Teaching through 21st-Century Competence: Insights from All Male Instructional Design Class - Putri, Hilma Pami (Asosiasi Ide Bahasa Kepri, 2024)
As the world becomes more interconnected, the ability to swiftly adapt to changes has never been more crucial. Consequently, the Indonesian government has proposed that all educational institutions promote 21st-century competencies in every subject, including English lessons. In language teaching classes, preservice teachers must evolve to meet the demands of future competencies, which are essential for participating in global commerce, diplomacy, and multicultural societies. These competencies include critical thinking, collaboration, creativity, and communication. This study aims to investigate how preservice teachers conceptualize these competencies and the strategies they use to enhance language teaching. The data was gathered from male students enrolled in an Instructional Design Class who received material on 21st-century skills. The findings reveal that all male instructional designers meet the demands of future competencies and are actively incorporating strategies to develop these skills in their language teaching practices. These strategies include integrating technology, promoting a scientific approach, and preparing for the demands of an interconnected, globalized world. However, there is still a need to focus on effective teaching techniques to achieve the desired learning outcomes in language education. This study highlights the importance of continuous adaptation and innovation in teaching methodologies to equip students with the necessary skills for the future.